KONSEP REDUCE, REUSE DAN RECYCLE DALAM PEMANFAATAN SAMPAH/LIMBAH RUMAH TANGGA SEBAGAI MEDIA PEMBELAJARAN DALAM MENINGKATKAN KREATIFITAS ANAK DAN RASA KEPEDULIAN TERHADAP LINGKUNGAN DAN MASYARAKAT - Rachmasari Pramita Wardhani; Kusnadi; Dullen Arkadius; Erwin Gustianta (Universitas Tridharma, 2021)
The learn from home activity which is part of the teaching system that was in effect during the Covid 19 pandemic is a demand for parents of students to be able to act as educators and demandthat parents be able to think creatively so that children don't feel bored studying at home. A closeness between parents and children can be rebuilt when parents can fully assist children in the learningprocess. As for the other benefits of this program, it can foster children's awareness of theenvironment, namely that children as students understand that used goods are reused to be used astoys so that they care more about existing used goods, educate children to be creative becausechildren are able to make items from Used goods or trash, children are also accustomed to not havinga consumptive lifestyle because they are able to make their own items or games from used goodswhose materials can be obtained from the surrounding environment, educate children to love andprotect the environment starting from the surrounding environment, educating children in developingideas to continue working and innovating, educating children to be smart, independent and skilledgenerations. Keywords— reduce, reuse, recycle, trash, creativity, child